2018
DOI: 10.1002/slct.201801349
|View full text |Cite
|
Sign up to set email alerts
|

Azidoacetic Acid Amides in the Synthesis of Substituted Arylidene‐1‐H‐imidazol‐5‐(4H)‐ones

Abstract: We present a novel efficient method for the synthesis of substituted arylidene‐1‐H‐imidazol‐5‐(4H)‐ones based on the use of azidoacetic acid amides. The proposed approach was successfully used for the preparation of three rows of target substances with different substituents in the imidazolone ring and benzylidene moiety. The presented methodology tends to be multipurpose and convenient for the introduction of substituents in any position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Furthermore, the hydrogen bond strengthening or weakening could also be revealed based on monitoring the spectral shifts of vibrational modes involved in the formation of hydrogen bonds . The vibrational spectra of bip chromophore in the conjunct vibrational regions of the O‐H stretching mode have been shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, the hydrogen bond strengthening or weakening could also be revealed based on monitoring the spectral shifts of vibrational modes involved in the formation of hydrogen bonds . The vibrational spectra of bip chromophore in the conjunct vibrational regions of the O‐H stretching mode have been shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Different from experimental results, the specific potential barrier of ESIPT and comprehend the mechanism of the ESIPT process can be provided based on quantum chemical computational study. And previous theoretical investigations have indicated that TDDFT/B3LYP calculated level should be efficient as far as the form of hydrogen‐transfer potential energy curves is concerned . It can provide qualitative energetic pathways for the ESIPT process of bip chromophore.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations